Ukrainian predecessors of the deep ecology’s idea - Yu. K. Duplenko (History of science and technology, 2017)
On the basis of the analysis of the working text “Human work and its relation to the energy distribution” the author of article supports the opinion of modern researchers that S. Podolinsky’s ideas published in his work (1880) had been foreseen by V. Vernadsky’s noosphere concept, I.Prigozhin’s synergetic approaches and A. Naess’s deep ecology.